School and Student Families’ Communication Techniques and Relevant Practices in a Social Pedagogical Context: Primary School Principals’ Views in Greece during the Economic Crisis (International Journal of Social Pedagogy, 2015)
The current paper researches and discusses primary school principals’ views in Greece, regarding the school and student families’ communication techniques and relevant practices during the economic crisis, based on the comparison of research findings with corresponding findings from international research. More specifically, it measures the extent to which the principals use communication techniques and practices to communicate with the students’ parents, as well as the usage rate of ways to approach active parents, parents who avoid contact with the school, parents who would like more involvement with the school. Moreover, it contemplates how principals’ views differentiate depending on their gender, their overall experience in their duties, their experience in their current position, as well as their school’s level of communication with the students’ parents. The study included 80 participating principals, who served in primary schools of Cyclades (an island group in the Aegean Sea) during the first semester of 2011. The results show that, apart from gender, all the above factors differentiate the principals’ views regarding the usage rate of the school’s communication techniques and practices with the parents. The findings also depict the frame and the communication limits, which the principals in Greece seek to achieve with the students’ parents.